Appendix I: Hovudfag/master i Samfunnsplanlegging og lokalsamfunnsforsking/kulturforståing ved UiT 1975–2024 - Aarsæther, Nils (Septentrio Reports, 2024)
Liste over avlagte hovedfags-/mastergradsoppgaver ved UiT i årene 1975–2024.